2008
DOI: 10.1007/s11010-008-9871-9
|View full text |Cite
|
Sign up to set email alerts
|

The Src tyrosine kinase pathway regulates thecal CYP17 expression and androstenedione secretion

Abstract: In order to evaluate the role of Src tyrosine kinase in thecal cell steroidogenesis, a pharmacological approach was utilized by treating enriched populations of mouse ovarian theca-interstitial cells in vitro with a direct Src kinase inhibitor, PP2. Inhibition of Src with PP2 increased both basal and forskolin-stimulated androstenedione secretion, and increased cytochrome P450 17-alpha hydroxylase-lyase (CYP17) promoter activity and steady state mRNA. PP2 did not change thecal levels of StAR mRNA. Inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…mRNA level of genes ( Cyp17 , Cyp19 , StAR , and LHR ) related to androgen production in the ovary were measured by iQ SYBR green according to the manufacturer’s protocol (Bio-Rad). Primers for Cyp17 were sense 5′-GATCTAAGAAGCGCTCAGGCA3′ and antisense 5′-GGGCACTGCATCACGATAAA-3′ ( 22 ), for Cyp19 sense 5′-TTGGAAATGCTGAACCCCAT-3′ and antisense 5′-CAAGAATCTGCCATGGGAAA-3′ ( 23 ), for StAR sense 5′-CCCAAAGAAGGCATAGCAAG-3′ and antisense 5′-GCTGAATCCCCCAAACTTCT-3′, and for LH receptor (LHR) sense 5′-GACCAAAAGCTGAGGCTGAGA and antisense 5′-CAATGTGGCCATCAGGGTAGA-3′ ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…mRNA level of genes ( Cyp17 , Cyp19 , StAR , and LHR ) related to androgen production in the ovary were measured by iQ SYBR green according to the manufacturer’s protocol (Bio-Rad). Primers for Cyp17 were sense 5′-GATCTAAGAAGCGCTCAGGCA3′ and antisense 5′-GGGCACTGCATCACGATAAA-3′ ( 22 ), for Cyp19 sense 5′-TTGGAAATGCTGAACCCCAT-3′ and antisense 5′-CAAGAATCTGCCATGGGAAA-3′ ( 23 ), for StAR sense 5′-CCCAAAGAAGGCATAGCAAG-3′ and antisense 5′-GCTGAATCCCCCAAACTTCT-3′, and for LH receptor (LHR) sense 5′-GACCAAAAGCTGAGGCTGAGA and antisense 5′-CAATGTGGCCATCAGGGTAGA-3′ ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…PD98059 is a specific inhibitor of the p44/42 MAPK signaling pathway, which can inhibit phosphorylation of MEK, MAPK, and the downstream molecules, therefore altering the regulatory roles of the MAPK signaling pathway. A recent study showed that PD98059 decreases phosphor-MAPK in ovarian theca cells [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of ERK cascade may involve other signaling molecules such as SFKs, β-arrestins, PKA, Ras, Shc and the EGFR as intermediates in the pathway [ 64 - 69 ]. Studies carried out employing inhibitors and dominant negative constructs of SFKs have shown that many of these molecules interact with the canonical LH/CGR activated signaling pathway resulting in altered responsiveness to steroidogenesis in ovarian cells [ 19 , 70 , 71 ], MA-10 tumor Leydig cells [ 18 , 72 , 73 ] and adrenal cells [ 74 , 75 ]. In the present study, expression of genes belonging to SFKs confirm low levels of activated Src during high steroidogenic state or increased activated levels of Src during low steroidogenic state of the CL.…”
Section: Discussionmentioning
confidence: 99%